Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

12,525 questions

17,245 answers

1,424 comments

28,668 users

general form of (x-2)^2 + (y-4)^2 =36

0 votes
asked Oct 12 in BASIC MATH by anonymous

1 Answer

0 votes

 

(x-2)^2 + (y-4)^2 =36

Expand the equation using following formula.

(a-b)^2=a^2-2ab+b^2

(x-2)^2=x^2-2(x)(2)+2^2

             =x^2-4x+4

(y-4)^2=y^2-2(y)(4)+4^2

             =y^2-8y+16

(x-2)^2 + (y-4)^2 =36

x^2-4x+4+y^2-8y+16=36

x^2+y^2-4x-8y+20=36

x^2+y^2-4x-8y-16=0

 

 

 

 

answered Oct 13 by homeworkhelp Scholar
reshown Oct 13 by bradely

Related questions

...